Providing a paradigmatic model of return on investment in the training of employees in the petrochemical industry - Mehdi Farahani; Seyyed Ali Akbar Ahmadi; Mohammad Tamimi (مدیریت و چشم انداز آموزش)
The current research was conducted with the aim of providing a model of return on investment in the training of employees in the petrochemical industry. This research was based on an empiricist philosophy, fundamental from the goal point of view, and with a deductive-inductive approach with a mixed research method. The research data in the qualitative part was collected through interviews with 17 management professors (theoretical experts) and managers of the petrochemical industry (experimental experts) who were selected by purposive sampling. Also, the indicators identified by fuzzy Delphi method with the participation of qualitative department experts were validated and prioritized by fuzzy Swara method. Finally, the final research model was presented. To achieve the objectives of the research, by analyzing the interviews with experts, a set of useful indicators of return on investment in employee training was identified. The main categories of this research are indicators of return on investment in employee training, grouped in the form of eight main categories: organizational infrastructure, strategic alignment, training and development of human resources, incompatibility of human resources, employee empowerment, process-oriented strategy, return on investment to Company, and gain competitive advantage. The findings have shown that training and development of human resources is an underlying variable that affects the empowerment of employees and process-oriented strategy. In the meantime, it is important to strengthen the organizational infrastructure and create strategic alignment to achieve return on investment in employee training. By implementing the mentioned items, the return of capital to the company and gaining a competitive advantage will be achieved. The ranking of indicators of return on investment in employee training with the Swara Fazi method showed that the support factors of senior management, informing employees of the results of training goals, continuous training with wide applications are of the highest importance. Extended abstract Introduction In order to find out the adequacy of the training and improvement programs of the organization's employees, their effectiveness should be evaluated. One of the important factors in this field is to pay attention to the return of training investment, which is considered as an important model in evaluating the effectiveness of employee training. In recent years, paying attention to the rate of return on investment in organizations has become a fundamental issue for managers (Imani, Rezaei, & Sharifi, 2020). Despite the importance of return on investment in education, this issue is still unknown in the organizational field. This is due to issues such as the lack of evaluation tools, the inability of evaluators to involve investors, and the inability to implement inclusive approaches to education. On the other hand, few academic studies have been done in this field, and a deep research gap is observed in this field. In this regard, the National Petrochemical Company of Iran, which is the most efficient developmental organization in the field of petrochemicals in West Asia, faces the same problem of measuring and evaluating the practical results of training courses, which are often very expensive. Therefore, the question that this research is trying to find an answer for is, what elements and components does the investment return process in the training of petrochemical industry employees include, what conditions are it affected by, and what are the quantitative and qualitative criteria for evaluating the results of the training?